Suppose f(x)=x^2-3x-2 and g(x)=4x+1. Determine (f-g)(-2)

akay2016

New member
Joined
Jan 31, 2016
Messages
1
So I have this problem I am not sure how to approach. Please Help

Suppose f(x)=x^2-3x-2 and g(x)=4x+1. Determine (f-g)(-2).

Any Help would be nice!

Thanks
 
So I have this problem I am not sure how to approach. Please Help

Suppose f(x)=x^2-3x-2 and g(x)=4x+1. Determine (f-g)(-2).

Any Help would be nice!

Thanks

What is the expression for:

f(x) - g(x) = ?
 
So I have this problem I am not sure how to approach. Please Help

Suppose f(x)=x^2-3x-2 and g(x)=4x+1. Determine (f-g)(-2).
This is called "operating on functions", which is the application of addition, subtraction, multiplication, and division (the mathematical "operations") to functions. (lesson)

Do you know how to find f(-2) and g(-2)? If so, what values did you get? Apply what is explained in the lesson link above to these values. Simplify to get the answer. ;)
 
Top